2012
DOI: 10.1002/pssb.201248154
|View full text |Cite
|
Sign up to set email alerts
|

Circuit model for hybridization modes in metamaterials and its analogy to the quantum tight‐binding model

Abstract: We formulate a general method to analyze hybridization modes in metamaterials by employing electrical circuit models. By rewriting circuit equations for coupled inductor–capacitor circuit networks in the bra‐ket notation, we show that there exists a good analogy between circuit models and quantum tight‐binding models in solid‐state physics. Our picture is also applicable to transmission systems that do not have tightly bound eigenmodes. This analogy enables the synthesis of various electromagnetic metamaterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We follow the method given in Ref. 55 , where the periodical circuit lattice problem is transformed into a tight-binding-like model in the momentum space. This approach relies on an analogy between Kirchhoff current equation in periodic circuit lattice and the quantum mechanics with periodic crystalline structure, from which the circuit band structure arises in a manner analogous to electronic band structure in crystals.…”
Section: Models and Theoretical Frameworkmentioning
confidence: 99%
“…We follow the method given in Ref. 55 , where the periodical circuit lattice problem is transformed into a tight-binding-like model in the momentum space. This approach relies on an analogy between Kirchhoff current equation in periodic circuit lattice and the quantum mechanics with periodic crystalline structure, from which the circuit band structure arises in a manner analogous to electronic band structure in crystals.…”
Section: Models and Theoretical Frameworkmentioning
confidence: 99%
“…Circuit network theory is a common way to model metamaterial properties [36][37][38][39][40][41][42]. Equation (2) and the structure depicted in Fig.…”
Section: Electrodynamic Model For Field-matter Interactionmentioning
confidence: 99%
“…In previous work [16], utilizing electrical circuit models, we showed that the dispersion relations of metal structures with various lattice symmetries have flat bands. We confirmed the formation of the electromagnetic flat bands for a metallic kagomé lattice by illumination of propagating waves theoretically and experimentally [17].…”
Section: Introductionmentioning
confidence: 97%